2018
DOI: 10.3897/mbmg.2.26869
|View full text |Cite
|
Sign up to set email alerts
|

A DNA metabarcoding protocol for hyporheic freshwater meiofauna: Evaluating highly degenerate COI primers and replication strategy

Abstract: The hyporheic zone, i.e. the ecotone between surface water and the groundwater, is a rarely studied freshwater ecosystem. Hyporheic taxa are often meiofaunal (<1 mm) in size and difficult to identify based on morphology. Metabarcoding approaches are promising for the study of these environments and taxa, but it is yet unclear if commonly applied metabarcoding primers and replication strategies can be used. In this study, we took sediment cores from two near natural upstream (NNU) and two ecologically im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 76 publications
2
36
0
Order By: Relevance
“…The remainder of the metazoans were mainly branchiopods and copepods. Similar results with non-target taxa were reported in other papers using degenerate COI primers for freshwater community metabarcording (Weigand & Macher, 2018). There has been some debate about the usability of the standard COI barcode region defined by Hebert et al (2003) within DNA- and eDNA-based analyses, but thus far the benefit of an extensive COI database seems to outweigh the drawbacks (Andújar et al, 2018), as also witnessed by the many primer sets that have been designed for macroinvertebrate metabarcoding studies (Leray et al, 2013; Bista et al, 2017; Elbrecht & Leese, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The remainder of the metazoans were mainly branchiopods and copepods. Similar results with non-target taxa were reported in other papers using degenerate COI primers for freshwater community metabarcording (Weigand & Macher, 2018). There has been some debate about the usability of the standard COI barcode region defined by Hebert et al (2003) within DNA- and eDNA-based analyses, but thus far the benefit of an extensive COI database seems to outweigh the drawbacks (Andújar et al, 2018), as also witnessed by the many primer sets that have been designed for macroinvertebrate metabarcoding studies (Leray et al, 2013; Bista et al, 2017; Elbrecht & Leese, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…sample, sub‐sample, or PCR. This result is consistent with Weigand and Macher () who found that taxon detection among PCR replicates mostly overlapped. However, we did find that detection of taxa increased slightly as levels of replication were combined.…”
Section: Discussionsupporting
confidence: 92%
“…Trombidiformes, Dugesia , see Table S3 in Elbrecht and Leese), where detection rate clearly decreased with increasing filtering thresholds. Furthermore, taxa which are known to amplify less successfully with the universal BF2/BR2 primers (Nematoda, Gastropoda, see Elbrecht and Leese (), Weigand & Macher, ) were less frequently detected. The highest number of taxa was constantly detected in samples processed with the TruSeq Nano DNA Library Preparation kit (threshold 0.004–0.01: on average 48.9 [±1] taxa, threshold 0.02–0.09:46.4 [±1.2 taxa]).…”
Section: Resultsmentioning
confidence: 99%